The Effect of Liquidity, Leverage, and Profitability on Stock Return of Production Goods Trade Companies Listed on the Indonesia Stock Exchange - Tasya Ramian Siagian; Robinhot Gultom; Winarto Winarto; Mitha Christina Ginting (Fakultas Ekonomi Universitas Simalungun, 2026)
This study investigates the partial and simultaneous effects of Liquidity (Current Ratio/CR), Leverage (Debt to Asset Ratio/DAR), and Profitability (Return on Assets/ROA) on Stock Return within the Large-Scale Production Goods Trade Subsector listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. A quantitative causal research design employing multiple linear regression analysis via IBM SPSS Statistics version 26 was adopted. Purposive sampling yielded a final sample of 22 companies comprising 60 valid firm-year observations after outlier removal. Partial hypothesis testing reveals that Liquidity (CR) exerts a negative and insignificant effect on Stock Return; Leverage (DAR) exerts a negative and statistically significant effect; and Profitability (ROA) exerts a positive and statistically significant effect. Simultaneously, all three independent variables significantly influence Stock Return, with an Adjusted R² of 14.7%, indicating that 85.3% of return variation is attributable to factors outside the present model